Investigating the impact of lean practices and industry 4.0 technologies towards operational performance - Sharah Qistina, Shari Fuzzaman; Noraini, Mohd Razali; Kartina, Johan (Springer, 2025)
The integration of Industry 4.0 technologies and Lean practices in Malaysia's manufacturing industry is the subject of this study. The primary objective is to investigate how incorporating these practices might enhance operational effectiveness, lower expenses, and enhance product quality. A survey was developed and distributed to various manufacturing firms, collecting both qualitative and quantitative data on the application and perceived benefits of Lean Practices such as 5S, Kanban, and Just-in-Time (JIT), as well as Industry 4.0 technologies including the Internet of Things (IoT), Big Data Analytics and Cloud Computing. Data analysis was performed using Excel to identify patterns and correlations. The findings show that the combined use of Lean Practices and Industry 4.0 Technology leads to a significant increase in operational efficiency, cost reduction and product quality improvement with a percentage of response to the perceived impact of 75%, 89% and 96%, respectively. It was also found that 5S and system integration are the most frequently implemented practices in the industry compared to other practices. However, challenges such as integration strategies and infrastructure limitations were also identified. The study concludes that although the integration between Lean and Industry 4.0 offers great benefits, ad-dressing the challenges highlighted is essential to maximize their potential in the manufacturing sector.